Children, Social Assistance and Outcomes: Cross National Comparisons - Roderic Beaujot; Jianye Liu (Luxembourg Income Study (LIS), 2002)
The prevalence of low income for children, especially for children in lone-parent families, varies considerably across countries. This paper considers five sets of hypotheses that may explain this cross-national variability of child poverty. The tentative conclusion from this analysis in 20 countries is that reducing child poverty, and in lone-parent families in particular, requires several approaches. Provisions that would discourage teenage childbearing would have their importance, as would opportunities for lone mothers to work. More important is the generosity of social expenditure applying to individuals and especially to families. The present analysis also shows the advantages of encouraging joint custody, along with special provisions for lone parents, and child support through advance maintenance payments.
Keywords: 330; Kinder; Armut; Alleinerziehende; Familienleistungsausgleich; OECD-Staaten